Pengaruh Implementasi Standar Akreditasi, Nilai - Nilai Islam Dan Pengalaman Pasien Terhadap Loyalitas Pasien Rumah Sakit Rumah Sehat Terpadu Dompet Dhuafa - Mahary, Wasiah; Indupurnahayu, Indupurnahayu; Suherman, Suherman (Jurnal Manajemen, 2022)
Implementation of Accreditation Standards, Islamic Values and Patient Experience are important things that can influence patient decisions in choosing a hospital. The purpose of this study was to analyze the effect of implementation of hospital accreditation standards, the effect of implementation of Islamic values, and the effect of inpatient experience on inpatient loyalty at the Rumah Sehat Terpadu Dompet Dhuafa. Data was collected through interviews using a questionnaire and analysis of hypotheses using SPSS tools to 110 patients or families of inpatients as respondents. Data analysis uses quantitative methods, descriptive approaches and associative analysis, because there are variables that will be studied to present an overview of the relationship between these variables. The results showed that there were F test results on the variables of patient experience, implementation of accreditation standards and Islamic values simultaneously on patient loyalty. The results of the R Square test are 0.280, meaning that the variable implementation of accreditation standards, Islamic values and patient experience simultaneously affects the patient loyalty variable is 28%. The results of the T-test showed that the variables of implementation of accreditation standards and Islamic values have no effect on patient loyalty, while the patient experience variable has an effect on patient loyalty.